Research on Employee Sense of Gain: The Development of Scale and Influence Mechanism - Gu, Yinhua; Yang, Yingyao; Wang, Jing (Frontiers in Psychology, 2020)
Employee satisfaction is a main source of firms’ competitive advantages. Employee sense of gain (ESG) is defined as the subjective feeling of getting various objective benefits due to employees’ efforts at work. It appropriately reflects employee satisfaction with the objective needs and their subjective perception of the firms, which affects their attitude, behavior, and work performance. Although ESG is gaining increasing interest in human resources research and managerial practice, literature on its conception, measurement and contribution to human resource theory is still limited. The study 1 developed an integrative framework of concept of ESG and reported the development and validation of a scale measuring ESG. Based on the exploratory factor analysis of 201 valid questionnaires responded by enterprise staffs, the initial scale was formed. Through confirmatory factor analysis of 172 questionnaires, the formal scale was obtained. The multi-phase scale development process which resulted in a 14-item ESG scale measuring two dimensions: employee’s material sense of gain and employee’s spiritual sense of gain. Study 2 investigated the influence mechanism of ESG based on statistical analysis of 254 valid questionnaires. The results showed that ESG was influenced by the all three dimensions of supportive human recourse practices (SHRP), whereby the influences were mediated by perceived insider status (PIS). Results also suggested that leader political skill (LPS) moderated the effect between SHRP (fairness of rewards and punishments, growth opportunity) and PIS positively. Overall, this research provided a reliable and valid measurement scale of ESG in Chinese setting and explored the influence mechanism, as well as boundary conditions. Managerial implications were provided from the perspectives of organizations, leaders, and employees.